Transcranial sonography in Parkinson’s disease - I. V. Bayborodina; V. D. Zavadovskaya; N. G. Zhukova; I. A. Zhukova; T. V. Fetisova; V. N. Yazhinova; T. D. Ochirova; A. V. Danilenko; A. V. Basanova; L. A. Zangeeva (Бюллетень сибирской медицины)
Despite a broad discussion of the results of ultrasound in Parkinson disease, the dynamics of hyperechoinality of the substantia nigra based on the clinical forms and stages of the disease remains controversial.The purpose of this study is to study thechanges in the substantia nigra of the brain based on the clinical form and stage using an ultrasound in patients with Parkinson’s disease.Materials and methods. The study involved 100 patients with Parkinson’s disease whom were scanned using transcranial sonography through the temporal window with the use of ultrasound scanner Toshiba Aplio 500 (Japan) with a sector transducer with a frequency of 2,5 мGz.Results. It was found that the asymmetric variant of changes in the black substance prevailed in each clinical group of patients and was more often recorded with akinetic-rigid form and the greatest changes were observed in the stages  II and III of the disease.